Blockchain Technology Transformation in Advancing Future Change - Taqwa Hariguna; Yusuf Durachman; Muhamad Yusup; Shofiyul Millah (IAIC Bangun Bangsa, 2021)
With the development of technology in the 4th century, it can be seen from before the christian period (SM) such as the compass, calendar, pozzolana and wheel. And now the world is about to undergo a tremendous transformation. In this extraordinary change there are inventions such as printing machines, machines, digital computers, vaccines, telegraph technology, ironing tools, airplanes, and even the internet. With this discovery, the world underwent a tremendous transformation from the previous century, due to technological advances over time. Inventions made before Christ must take a long time, even centuries, but making changes today only takes a few years. But in this study, we will describe blockchain technology even centuries, but by making changes now it only takes a few years. But this research will describe blockchain technology. On Facebook, which has a new change to the concept of decentralization, but this concept is still somewhat contradictory to the current world system, so why do users need intermediaries, namely third parties to keep the transaction secure? This research will provide answers to arguments starting with a conceptual understanding which will then go through the stage of case study stages in various industries such as administration, banking, chain management, intellectual management, transportation, even asset management, logistics and energy materials. With blockchain technology, it is used to describe blockchain technology and technology that humans do everyday. There is a concept of a ledger that undergoes a gradual transformation carried out by Satoshi Nakamoto, who has a triple entry ledger that is used to master blockchain technology. In blockchain technology, it has cryptography that is useful for avoiding money laundering, knowing customer activity, knowing all banking transactions and even administration in storing people's identities. In this case study, we will discuss big companies such as IBM, Amazon, Maersk, and even a kind of startup like Ezremit and Signazy. And in this administration section it is important to identify global educational techniques and develop technology in a better direction so that it can advance society in Indonesia and blockchain technology is included in technology that advances future change.